An Empirical Study on Software Engineering in Mobile Applications and Future Research Directions - Balamurugan, R; Ravichandran, M (International Journal of Computer Sciences and Engineering, 2019)
Nowadays, mobile devices have reached its popularity in greater heights, specifically the usage of smart phones has extended its features in communication technology with rapid evolution. With regards to this, the developers are always passionate about providing the smart ways and approaches through the Mobile App for the common users so that they have smart lifestyle. To provide the smart apps which works on smart devices, the diversity is there in the usages of tools and technologies. In addition to hardware rapid evolution, mobile applications are also increasing in their complexity and performance to cover most the needs of their users. Both software and hardware design focused on increasing performance and the working hours of a mobile device. Different mobile operating systems are being used today with different platforms and different market shares. Like all information systems, mobile systems are vulnerable to several issues. In this paper survey on software engineering paradigm in mobile applications are discussed by analyzing various existing approaches in the field of mobile software testing, mobile software quality assurance and mobile application security threats.